Factors of students' academic success in university / Tang Howe Eng ...[et al.] - Tang, Howe Eng; Daneil, Imelia Laura; Ibrahim, Khalik (2016)
This research intends to determine the factors of students' success in university to help university top management and students to monitor and predict their academic grade points during their university years. This research also aims to investigate if there is any relationship between the factors and the academic success of the university students. This research employs quantitative method design whereby quantitative data will be collected at the same time. The result from the quantitative data is used to determine the factors of students' success and compare the interventions that could play the roles to improve university students' academic success. The population of this research consists of the public university students in Sarawak. Random sampling method is used to select a total of200 samples from public universities for all the clusters. The samples are full-time public university students who have successfully completed their diploma studies and undergraduate degrees. Data are collected through an academic year. The instrument of this research consists of questionnaire distributed to collect information on the possible factors of academic success of university students. The possible factors are ranging from demographic variables, biographic variables, institutional variables and personality related variables. The data analysis includes the calculation of descriptive statistics, such as mean, percentage and standard deviation and inferential statistics, such as independent t-test or Mann-Whitney U Test, ANOVA or Kruskal Wallis Rank Sum Test subject to the normality of the samples. The step-wise regression modelling is used to analyze the data collected. The expected outcome from this research is the identified factors of the academic success of the university students which can assist the top managements and university students to monitor, plan and forecast their academic results. This system is hoped to motivate the university students to be more systematic and deterministic in planning their academic progress.